+0  
 
0
420
1
avatar

6log3(x−3)=−24

Guest Mar 5, 2015

Best Answer 

 #1
avatar+94120 
+5

Do you mean 

$$\\6log_3(x-3)=-24\\\\
log_3(x-3)=-4\\\\
3^{log_3(x-3)}=3^{-4}\\\\
x-3=3^{-4}\\\\
x-3=\frac{3^{-4}}{1}\\\\
x-3=\frac{1}{3^{+4}}\\\\
x-3=\frac{1}{81}\\\\
x=3\frac{1}{81}\\\\$$

Melody  Mar 6, 2015
 #1
avatar+94120 
+5
Best Answer

Do you mean 

$$\\6log_3(x-3)=-24\\\\
log_3(x-3)=-4\\\\
3^{log_3(x-3)}=3^{-4}\\\\
x-3=3^{-4}\\\\
x-3=\frac{3^{-4}}{1}\\\\
x-3=\frac{1}{3^{+4}}\\\\
x-3=\frac{1}{81}\\\\
x=3\frac{1}{81}\\\\$$

Melody  Mar 6, 2015

9 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.